2021
DOI: 10.1016/j.dib.2021.107502
|View full text |Cite
|
Sign up to set email alerts
|

Concentration dataset of 8 selected trace elements in cultured rainbow trout (Oncorhynchus mykiss) and dietary exposure risks in the Missouri adult population

Abstract: Highlights Concentrations of eight trace elements in O. mykiss from aquaculture. Only Cr, in some samples, exceeded the permissible limit. EWI values of analyzed trace elements were below the PTWIs. Arsenic was the highest contributor to non-carcinogenic risk in adult consumers. Cancer risk of As, Cd, Cr, and Pb in the adult population is probable. High intake per w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Fish feeds, at times, contain metals above the prescribed limits (Mannzhi et al, 2021;Maule et al, 2007). Other studies found chemical contaminants such as PCBs (McMullin et al, 2022) and total Hg (Ikem et al, 2021a) in feeds. Consequently, seafood may contribute to the total dietary intake of chemical contaminants in humans.…”
Section: Introductionmentioning
confidence: 99%
“…Fish feeds, at times, contain metals above the prescribed limits (Mannzhi et al, 2021;Maule et al, 2007). Other studies found chemical contaminants such as PCBs (McMullin et al, 2022) and total Hg (Ikem et al, 2021a) in feeds. Consequently, seafood may contribute to the total dietary intake of chemical contaminants in humans.…”
Section: Introductionmentioning
confidence: 99%